Ritual, Bid‘ah, and the Negotiation of the Public Sphere in Contemporary Indonesia - Jahroni, Jajang (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2018)
The politicisation of ritual has been common in Indonesia over centuries. In the 18th century, the Padri people in West Sumatra introduced a puritan Islam creating a long-standing conflict between the Padris and the local Muslim groups in the region. In the early 20th century, the modernists criticized the religious practices of the traditionalist Muslims. In the 1980s, a new group of Salafi people bring back the issues of bid‘ah into the Islamic discourses of Indonesian Islam. Adhering to literal interpretations of Islamic teachings, Salafi groups question the validity of rituals associated with traditionalist Muslims, thereby exerting their power over Muslim believers. In response, traditionalists defend their opinions by expanding the definition of bid‘ah. Mosques, one of the most strategic institutions in Islam, have provided sites of contestation between traditionalists and Salafis. This has resulted in the politicisation of mosques over the last decades. Having different understandings of rituals, traditionalists and Salafis have used different methods to facilitate social engagement and organizational capacity.DOI: 10.15408/sdi.v25i1.5308